PENGARUH PEMBERIAN BEBERAPA DOSIS PUPUK NPK TERHADAP PERTUMBUHAN BERBAGAI SUMBER TUNAS TANAMAN NANAS (ANANAS COMOSUS (L) MERR) YANG DITANAM ANTARA TANAMAN SAWIT BELUM MENGHASILKAN DI LAHAN GAMBUT - Cahyono, Eko Agus; Silvina, Fetmi; ', Ardian (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This study aim to get the best combination of fertilizer and various of Pineapple (Ananas comosus (L) Merr)between Immature Palm Oil Plantation. Studied lasted from July to October 2013 at the Experimental land Rimbo Panjang, University of Riau. The material used are sucker and slip, varieties Queen and NPK Mutiara fertilizer (16-16-16). The study arranged experimentally using Randomized Block Design (RBD) first factor is NPK fertilizer dose treatment, second factor are sources of shoots T1 (sucker) andT2 (slip). Parameter observed is quantitative parameters consist by added height of plant (cm), added leaves length of plant (cm), added leavesamount of plant (sheet), added leaveswidthof plant (cm) and leaves vastof plant (cm2). Data were analyzed using theF test and test of Duncan’s New Multiple Range Test (DNMRT) 5% level.The results shows that a combination giving NPK fertilizer and sources shoots treatment significantly affected to all parameters. Aplication NPK fertilizer 10 g/plant with a source of sucker is the best combination for growing pineapple on peat land. Keywords: Pineapple, source of bud, dose of fertilizer